Long-term effectiveness, safety, perfection, satisfaction and cost of electronic cigarette among single and dual users in Malaysia - Nik Mohamed, Mohamad Haniki; Rahman, Aziz; Jamshed, Shazia Qasim (EU European Publishing, 2018)
Background: More information is needed regarding long-term electronic cigarette (e-cig) effectiveness and safety for smoking cessation and reduction among single vs. dual users (SU vs. DU). This study assessed complete nicotine abstinence rate and safety of e-cig among both groups. Additionally, cigarette smoking abstinence and reduction, perception, satisfaction and cost were evaluated. Methods: A one-year observational study conducted among 220 e-cig users >18 to 65 years old recruited via convenience and snowball sampling from Kuantan and Pekan, Pahang, Malaysia. Follow-up visits were at week 4, 24, and 52. Validated questionnaires captured relevant information, including exhaled carbon monoxide and salivary nicotine levels, adverse events, perception, satisfaction and related cost. All subjects signed informed consent. Study approved by institutional research ethics committee. Analyses via SPSS (version 21), p < 0.05 considered as significant. Results: At week 52, 15.9% of SU (n=11) vs. 6.8% of DU (n=10) quit both tobacco and e-cig, OR: 2.57; p = 0.048. 34.8% of SU (n=24) vs. 17.1% of DU (n=25) quit only tobacco, OR: 2.58; p = 0.005. Among the DU, 23.3% (n=34) reduced ≥ 50% tobacco smoking vs. 21.7% of SU (n=15), OR: 1.092; p = 0.863. SU perceived less e-cig adverse events and withdrawal symptoms vs. DU. Subjects mainly reported coughing, breathing problems and craving for tobacco smoking. 33% of subjects were satisfied and rated e-cig as an effective smoking cessation aid. E-cig total monthly average cost was USD27 (MYR132.45). Conclusions: E-cig is effective and safe for long-term nicotine abstinence and tobacco smoking reduction. Subjects generally have good perception and satisfaction towards e-cig, especially among single users. Monthly expenditure on e-cig is less as compared to tobacco smokers.